A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia - Ng, Heok Hee; Tan, Heok Hui (Zootaxa, 2020)
A new species of Macrognathus of the M. aculeatus species group is described from the Kahayan River drainage in southern Borneo, Kalimantan Tengah, Indonesia. Macrognathus kris, new species, is distinguished from all Asian congeners in having the following unique combination of characters: rim of anterior nostril with two fimbriae and two fimbrules; 43–45 rostral tooth plates; 24–25 dorsal spines; 46–55 dorsal-fin rays; 51–59 anal-fin rays; 20–23 principal caudal-fin rays; 76–78 total vertebrae; body depth at anus 11.8–15.9% SL; color pattern consisting of light brown stripe on dorsum and 11–14 irregular pentagonal dark brown blotches on sides of body.